2012
DOI: 10.1089/acm.2011.0433
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nitric Oxide Synthase Attenuates Cutaneous Vasodilation During Warm Moxibustion-Like Thermal Stimulation in Humans

Abstract: These data demonstrate that NO is involved in the mechanism of cutaneous vasodilation induced by WMTS. Furthermore, increases in CVC despite inhibition of the COX pathway suggest that PG does not contribute to cutaneous vasodilation during WMTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The long-distance effect of moxibustion may be due to neural reflexes [25], whereas local effects are mediated through cytokines and signal transduction. The present study and previous studies have revealed moxibustion activates a unique cytokine profile and signal transduction pathways [22, 2734, 42, 43], as well as elevating macrophage autophagy (Figure 1) and natural killer cell activity [34]. These results suggest moxibustion generates a protective response against viral and bacterial infection, although it is not clear whether it functions locally or systemically.…”
Section: Discussionsupporting
confidence: 66%
“…The long-distance effect of moxibustion may be due to neural reflexes [25], whereas local effects are mediated through cytokines and signal transduction. The present study and previous studies have revealed moxibustion activates a unique cytokine profile and signal transduction pathways [22, 2734, 42, 43], as well as elevating macrophage autophagy (Figure 1) and natural killer cell activity [34]. These results suggest moxibustion generates a protective response against viral and bacterial infection, although it is not clear whether it functions locally or systemically.…”
Section: Discussionsupporting
confidence: 66%
“…Local inhibition of nitric oxide attenuates cutaneous vasodilator responses during postmenopausal hot flashes [ 38 ]. Otherwise, skin temperature, core body temperature, heart rate (HR), and blood pressure during warm moxibustion-like thermal stimulation at the site perfused with L-NAME were significantly decreased in healthy people [ 39 ]. These reports demonstrate that NO which is involved in the mechanism of visceral or local tissue vasodilation can be inhibited by L-NAME.…”
Section: Discussionmentioning
confidence: 99%
“…We have also recently demonstrated that NO is involved in the mechanisms of cutaneous vasodilation during warm moxibustion in the forearms of humans. 8 Thus, the local vasodilative reaction at the stimulation site may be induced by vasodilative substances, such as CGRP, released from sensory nerve endings through the axon reflex, but NO production may also be important. The mechanisms of cutaneous vasodilation are complex and many points remain unclear with regard to the action caused by acupuncture stimulation.…”
Section: Introductionmentioning
confidence: 99%